An axiological inquiry of Qur’ānic epistemology - Solihu, Abdul Kabir Hussain (2014)
This study inquires into the value system associated with two epistemological conceptual schemes of the Qur’ān, i.e., āyah (sign) and ḥikmah (wisdom). The claim that knowledge is neutral and that it is the person or society that decides its function has helped dissociate academic endeavours from social and religious values. In many respects, the rapid accumulation of all types of knowledge has led to intellectual crisis and epistemological confusion that marginalize or displace values from scientific inquiry. In this contemporary time, when some branches of knowledge are misused, there is a clarion call to revisit the place of values in epistemological discourse. In an attempt to broaden the human horizon, the Qur’ān propounds a unified system of knowledge and value whereby it draws attention to several natural phenomena seen as āyāt (signs) of Allah which should be explored through a ḥikmah-based framework of value judgment. Guided by axiological concern, this study examines the place of value in Qur’ānic epistemology.